2016
DOI: 10.1002/ajh.24595
|View full text |Cite
|
Sign up to set email alerts
|

Management of anemia in patients with congestive heart failure

Abstract: Anemia is an independent risk factor for adverse patient outcomes. There are no guidelines for management of anemia in patients with congestive heart failure (CHF), despite its high incidence. Four objectives were defined by the International Anemia Management and Clinical Outcomes Expert Panel (AMCO), a multinational group of interdisciplinary experts identified by the Society for the Advancement of Blood Management (SABM) to: determine the prevalence of anemia in outpatients; to determine the prevalence of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 59 publications
(71 reference statements)
1
31
0
7
Order By: Relevance
“…iron may improve functional status within four weeks, and reduces hospitalisations for cardiovascular reasons and mortality . In addition, improvements are maintained after 24 and 52 weeks .…”
Section: Should We Treat Iron Deficiency Without Anaemia?mentioning
confidence: 98%
“…iron may improve functional status within four weeks, and reduces hospitalisations for cardiovascular reasons and mortality . In addition, improvements are maintained after 24 and 52 weeks .…”
Section: Should We Treat Iron Deficiency Without Anaemia?mentioning
confidence: 98%
“…In patients with stages 4 and 5 CKD, metabolic abnormalities, anaemia, uraemic toxins, sympathetic overactivity and volume dysregulation all likely play a role in cardiac disease. Several studies evaluating anaemia in patients with HF have shown that anaemia is both common and independently associated with increased mortality 25. However, there are no consensus guidelines on transfusion thresholds for patients with HF.…”
Section: Risk Factors For Heart Failure In Patients With Kidney Diseasementioning
confidence: 99%
“…The symptoms associated with IDA include fatigue, palpitations, dyspnoea, headache, lack of concentration, dizziness, leg cramps, insomnia and pica . Treatment of IDA has been shown to improve energy, activity, quality of life (QOL), work capacity, cardiac function, sexual function, cognition and outcome in a variety of clinical settings …”
Section: Introductionmentioning
confidence: 99%
“…sexual function, cognition and outcome in a variety of clinical settings. [3][4][5][6][7] Oral iron is generally accepted as the treatment of choice for the majority of patients due to ease of administration, low cost and perceived effectiveness, but the incidence of side effects is considerable, thus, limiting adherence with long-term therapy. 8,9 A recent Cochrane Review raised doubts regarding the therapeutic value of oral iron for correcting postpartum anaemia.…”
mentioning
confidence: 99%